Liver and renal biochemical parameters in preeclampsia: a cross sectional study - Khan, Javid Ahmed; Ashraf, Aadil; Fayaz, Faizana; Qureshi, Waseem; Sheikh, Abu Talha (International Journal of Research in Medical Sciences, 2023)
Background: Pre-eclampsia is a multisystem disorder of human pregnancy with a genetic predisposition. It occurs more frequently in first pregnancies and leads to elevation in blood pressure and mainly affects maternal renal, cerebral, hepatic and clotting functions. This study evaluated biomarkers of renal and liver function among preeclamptic women. Methods: This was a cross-sectional study conducted among 150 preeclamptic women and 150 normotensive healthy pregnant women in hospital. The baseline data comprising age, gestational age, and blood pressure were obtained. Serum urea, creatinine, and plasma levels of liver enzymes ALT and AST, total protein, albumin, globulin and glucose were measured. Results: The plasma total protein, and albumin in preeclamptic group were significantly decreased (p<0.05) when compared with control. There was statistically significant increase (p<0.05) in urea creatinine, glucose, serum AST, and ALT activities in preeclamptic group. Conclusions: Preeclampsia has harmful effects on renal and liver function as shown by alteration of these parameters.